Germline transgenesis of the chordate Ciona intestinalis with hyperactive variants of sleeping beauty transposable element. Issue 1 (14th November 2012) - Hozumi, Akiko; Mita, Kaoru; Miskey, Csaba; Mates, Lajos; Izsvak, Zsuzsanna; Ivics, Zoltan; Satake, Honoo; Sasakura, Yasunori
Abstract Background: Transposon‐mediated transgenesis is an excellent method for creating stable transgenic lines and insertional mutants. In the chordate Ciona intestinalis, Minos is the only transposon that has been used as the tool for germline transformation. Adding another transposon system in this organism enables us to conduct genetic techniques which can only be realized with the use of two transposons. Results: In the present study, we found that another Tc1/mariner superfamily transposon, sleeping beauty (SB), retains sufficient activity for germline transformation of C. intestinalis. SB shows efficiencies of germline transformation, insertion into gene coding regions, and enhancer detection comparable to those of Minos. We have developed a system for the remobilization of SB copies in the C. intestinalis genome by using transgenic lines expressing SB transposase in the germ cells. With this system, we examined the manner of SB mobilization in the C. intestinalis genome. SB shows intrachromosomal transposition more frequently than Minos. Conclusions: SB‐based germline transformation and the establishment of a new method that uses its frequent intrachromosomal transposition will result in breakthroughs in genetic approaches that use C. intestinalis together with Minos. Developmental Dynamics 242:30–43, 2013. © 2012 Wiley Periodicals, Inc.